2012
DOI: 10.1039/c1cs15178a
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic thin-film combinatorial studies for rapidly optimising functional properties

Abstract: Combinatorial chemistry is now commonplace in the pharmaceutical industry and applied rigorously in the discovery of drugs. Within materials science, combinatorial methods have been widely applied in investigating thin-films and since its re-introduction in the mid 90's more than 20 new families of materials have been discovered. Yet, given the high diversity of states that can be produced in a single deposition, such methods are now being used more prominently to optimise functional properties of existing mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 213 publications
0
39
0
Order By: Relevance
“…Using this technique, Hyett et al. were able to synthesise a mixed anatase–rutile dense thin‐film with a composite gradient from 0 to 80 % rutile on a single film 21. Although their investigations indicated that no synergic enhancement was present within anatase/rutile mixtures, and that the pure anatase region yielded a more active photocatalyst, only five respective positions were examined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this technique, Hyett et al. were able to synthesise a mixed anatase–rutile dense thin‐film with a composite gradient from 0 to 80 % rutile on a single film 21. Although their investigations indicated that no synergic enhancement was present within anatase/rutile mixtures, and that the pure anatase region yielded a more active photocatalyst, only five respective positions were examined.…”
Section: Introductionmentioning
confidence: 99%
“…The combinatorial approach has been used extensively in aid of rapidly optimising a range of thin-film materials and to acquire a better understanding of the physical-functional property relationships involved. [21] One such approach has involved the use of combinatorial atmospheric pressure chemical vapour deposition (cAPCVD) to deposit thin-films with composition and thickness gradients. [22][23][24][25][26][27] Using this technique, Hyett et al were able to synthesise a mixed anatase-rutile dense thin-film with a composite gradient from 0 to 80 % rutile on a single film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, combinatorial and high throughput approaches were proven to be useful in the research of medicine, active compounds, materials, and devices. 4356 More relevant are combinatorial studies for the development of photovoltaics, such as bulk heterojunction solar cells, 5760 thin film solar cells, 49,6164 and related optoelectronic and photoelectrochemical devices. 44,47,6570 …”
Section: Introductionmentioning
confidence: 99%
“…They have been used in both the pharmaceutical industry, 33 and for protein crystallization trials, 34,35 and are also attracting increasing interest from the perspective of materials discovery, 36,37 where they have been shown to be well suited to the identification and optimization of inorganic thin films for applications such as catalysis. 38,39 Using calcium carbonate precipitated in the presence of amino acids (Asp, Glu, Asn and Val) as a model system, we have developed high throughput methods which enable us to precipitate crystals under a wide range of experimental conditions, to analyse the kinetics of the precipitation process using turbidimetry, and to determine the properties of the product crystals using electron microscopy, Raman spectroscopy and powder XRD. In particular, we have established protocols based on fluorimetry to rapidly evaluate the amounts of the additives occluded within the crystals, where this facilitates a detailed investigation of the dependency of occlusion on the solution conditions.…”
Section: Introductionmentioning
confidence: 99%